Temperature and environmental effects on glass fibre rebar: modulus, strength and interfacial bond strength with concrete - Abbasi, Abdolkarim; Hogg, Paul J. (Composites. Part B, Engineering, 2005)
In general, it is expected that concrete structures using glass fibre reinforced plastic (GFRP) rebar as reinforcement could have improved durability compared to normal steel reinforcement because of corrosion resistance of the rebar. However, there are some aspects of the behaviour of the GFRP bars under temperature and high alkali test conditions, which must be explored. This paper considers the effects of water and alkaline environments on the bond strength between the concrete and the rebar and strength and stiffness of the GFRP rebars at a range of different temperatures (20–120 °C). The three types of GFRP rods investigated in this work were subjected to alkaline solutions at 60 °C for three different exposure times, i.e. 30, 120 and 240 days. Tensile tests were carried out for physical–mechanical characterisation on the exposed rebar specimens. The aim of the study is to identify degradation processes and to show how accelerated ageing regimens can be used to differentiate between different GFRP rebar products in terms of durability. The results obtained from this work provide a base-line set of data which can be used in the future in conjunction with the thermal properties of the material to facilitate the modelling of the long-term properties of composite reinforced concrete structures at elevated temperatures. This will be particularly useful in the prediction of the performance of GFRP rebar reinforced concrete structures subject to fire